Influenza – A new pathogen every year. Issue 12 (December 2018) - Abreu, Rodrigo; Ross, Ted M.
Abstract: Host-pathogen interactions drive the outcome of infection. The complex interplay of the host immune system with the pathogen immune evasion mechanisms holds the key to understand when, how and why exposure leads to infection and disease. Influenza virus is capable of recurrent infection in presence of pre-immunity. Traditionally focused on the pathogen virulence factors, the influenza research field has recently realized the relevance of the host status during influenza virus infection and vaccination. Longitudinal tracking of human vaccination or influenza infection cohorts unveiled the importance of both humoral and cellular immunity as well as the impact of past-infection. These findings highlight the importance of host–pathogen interaction to understand disease and for the development of new vaccines. Highlights: Innate immune cells play a crucial role in viral clearance during influenza virus infection. CD4 memory T cells are directed to conserved antigens during influenza infection. Non-neutralizing antibodies can modulate innate immune response to decrease viral burden and ameliorate disease.